Amnesty Programme and Management of Niger-Delta Crises in Nigeria, 2009 – 2019 - Jude Chidi Onyenama; Evelyn Nwamaka Ochi Agbajeogu; Godwin Orakpowenri Orovwiroro (International Journal of Sustainable Applied Sciences, 2023)
This paper include to examine whether military presence escalated the crisis in Niger Delta; determine whether the Niger Delta crisis increase the poverty level of the region and examine the amnesty program has helped in addressing the Niger Delta Crises. Three research questions and three hypotheses were posited to guide the study. The literature review was done under conceptual review, empirical review and theoretical reviews. The research used ex post facto research method for the study. The findings among others includes that: (i) the presence of military has contributed to the crises situation in the Niger Delta region; (ii) the crises has negatively affected the economy of the Niger-Delta region; (iii) amnesty program has helped in addressing some of the Niger Delt crises through training of the youths and empowerment but the programme has not sufficently eradicate crises in the region. Base on, the work recommends among others that; (i) the federal government should be responsive to the people of Niger Delta agitation. The governments should ensure equitable inclusiveness of the Niger Delta region in the core political positions and in the Federal Government’s infrastructure delopment projects; (ii) the federal government should  consider the of alternative dispute resolution rather than the use of military; (iii) the amnesty programme should be reconstructed and effectively managed towards ensuring a standing structure for peaceful coexistence. Peace structures should be made paramount, so that the poverty and illiteracy of the community.